Implementation of a Critical Intercultural Approach Based on Women's Roles in Medellín (2019)
ABSTRACT: This action research report describes the experience during the implementation of a critical intercultural approach at Centro Formativo de Antioquia CEFA in Medellín. It was developed with a small group of female students from 11th grade. This project was based on women’s roles in our city and had four main sections where these roles were reviewed through time (past, present and future) along with their defining factors. Data were collected from a journal, surveys and students’ work. Although all the objectives for the project could not be achieved due to different limitations, findings showed that students perceptions about women’s roles changed during the development of the activities and lead them to different reflections. Moreover, they were more engaged in their learning process and improved their English knowledge by having the opportunity to express their ideas and using language in context.